The Digital Transformation of the Automotive Industry Catalysts, Roadmap, Practice - Winkelhake, Uwe (Springer International Publishing, 2018)
Building on his decades of experience as a consultant and project manager in the automotive industry, the author develops comprehensive and pragmatic recommendations for action regarding the digital transformation of the automotive and supplier industries. At the heart is the transition from a vehicle-focused to a mobility-oriented business model. Based on the catalysts of the digital change, four digitisation fields are structured, and a roadmap for their transformation is presented. The topics of comprehensive change in corporate culture and an agile and efficient information technology are covered in detail as vital success factors. Selected practical examples of innovative digitisation projects provide additional ideas and impulses. An outlook on the automotive industry in the year 2040 completes the discourse.